The social imagination and its representations in the paintings of students of the Department of Art Education (Al-Academy, 2023)
The aim of this research is to identify how to employ the social imagination and its representations in the paintings of the students of the Department of Art Education. Students of the Department of Art Education in the light of this tool, and the researcher reached a number of results, the most important of which are:1. The indicator of the social imagination in the excitement of the artist and the recipient, because the representations are embodied in forms within the painting and close to reality.2. An artistic sample of the representational imagination and the creative imagination was found to be more than the imaginary imagination.3. Individual symptoms related to the term.4. The representations of the social imagination were able to focus on social values and reject archaeological values, eliminating the positive energy of the artist and the audience.The research concluded with a review, recommendations and a list of references